The tadpole of Chiasmocleis carvalhoi and the advertisement calls of three species of Chiasmocleis (Anura, Microhylidae) from the Atlantic rainforest of southeastern Brazil - Wogel, Henrique; Abrunhosa, Patrícia A.; Prado, Gustavo M. (Phyllomedusa: Journal of Herpetology, 2004)
The tadpole of Chiasmocleis carvalhoi is figured and described for the first time from individuals collected in the State of Rio de Janeiro, southeastern Brazil. The advertisement calls of C. atlantica, C. capixaba, and C. carvalhoi also are described and compared with the advertisement calls of others Chiasmocleis species restricted to Atlantic Rainforest. The advertisement calls of C. atlantica, C. capixaba, and C. carvalhoi are similar, consisting of one pulsed note of harmonic structure emitted repetitively. Our study corroborates the monophyly of the genus Chiasmocleis based on similarities in advertisement calls. Calls of syntopic species (C. atlantica with C. carvalhoi and C. capixaba with C. schubarti) were less similar than those of closely related allopatric species.